PERBEDAAN MANIFESTASI KLINIS DAN LABORATORIS ANTARA PASIEN DEMAM BERDARAH DENGUE (DBD) DENGAN IgM+IgG+ DAN PASIEN DBD DENGAN IgM-IgG+ - SULISTYO , ACEP MEGYANA (2009)
Background: up to now DHF is still being a health problem for both health workers and society, because it may become an epidemic and bring high mortality. This disease have different clinical and laboratories manifestation according to it's risk factors. The mechanism of DHF is immune response both primary and secondary. Majority of DHF case occurs in secondary immune response that marked serologic test IgG+ (Immunoglobulin G positive). Purpose: the purpose of this study is to know the differences of clinic and laboratoric manifestation DHF patients with IgG+, either with IgM+ or IgM-. And to know number of DHF patients that perform serologic test IgM&IgG anti dengue. Method: retrospective study, observational analytic by cross-sectional method. The study analysis is medical records of DHF patients > 14 years old that perform serologic test IgM&IgG anti dengue at PKU Muhammadiyah Surakarta hospital and Dr. Moewardi general hospital on 2005, 2006, 2007, 2008, and 2009. Sampling technique use is non probability with consecutive sampling type. The data is provided in mean and persentage. Continuous variables analyzed by Mann-Whitney Test while nominal variables analyzed by Fisher's Exact Test & Chi-Square Test. The differences are consider significant if p<0,05. Result: the study population is 71 patients of DHF, it is divided 62 patients with IgM+IgG+ and 9 patients with IgM-IgG+. Fifty nine patients perform serologic test IgM&IgG anti dengue at PKU Muhammadiyah Surakarta hospital while at Dr. Moewardi general hospital are 15 patients. There are differences in epistaxis and gum bleeding between two group. Patients of DHF with IgM+IgG+ more often to have epistaxis and gum bleeding. Conclusion: patients of DHF with IgM+IgG+ have severe clinical manifestation than patients of DHF with IgM-IgG+.